PHP object oriented programming fundamentals. - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2016)
"The PHP OOP Fundamental course covers how to create advanced dynamic web pages using the modern day standard programming technique "Object-Oriented Programming". You will be learning new features and how to maintain and organize PHP code more efficiently in web projects. The curiosity of learning a new way to program an easier way will always make your coding days much more relaxed and less stressful. In the curriculum, we will covering each topic in details to make sure you full understand what is being taught in the lectures and how to use and apply these skills. We will be downloading and installing all the required software for this course. This software will help us create our enhanced newly featured dynamic web applications throughout our class lectures. This will benefit you because you will know what and how to download and install the required software needed to run these high powered web applications and also how to maintain and build these applications more efficiently. The most important skills you will learn throughout this course is knowing the new modern day approach of programming that most companies require from their programmers. Students will be able to build, design, create, and structure advanced dynamic web pages. Also know the basic concepts and skills that's needed to use this modern technique of programming. A live demonstration and example will always be performed in each section that the student can follow."--Resource description page.
Title from resource description page (Safari, viewed September 14, 2016).
Keywords: PHP (Computer program language); Scripting languages (Computer science); Programming languages (Electronic computers); Electronic books